Investigations of JIT applicability in supply chain: empirical evidence from Indian firms. (2016) - Mishra, Om Prakash; Kumar, Vikas; Garg, Dixit
Recent trend is to strengthen supply chain management by improving the processes of procurement of raw materials, manufacturing them into finished goods and distribution of these goods in the hands of the customers. Firms are paying much attention to make these processes speedy, responsive, low cost and transparent. In this paper, just in time has been used to boost the speed and accuracy of the above processes of supply chain. The positive effects of JIT in developed nations have prompted the researchers to focus its applicability in supply chain of Indian industries. JIT level, JIT benefits, JIT difficulties, JIT importance and JIT challenges are investigated. Survey of Indian firms is carried out which are practicing/implementing JIT at any level. The test results show that implementation of JIT level is high and firms are getting benefits by giving due importance of waste elimination, maintenance of low inventory, dissemination of sufficient information and compressing time taken. On the other hand, difficulties and challenges in JIT practices are also high.